2018
DOI: 10.1093/jas/sky086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein sources and nisin on rumen fermentation, nutrient digestion, plasma metabolites, nitrogen utilization, and growth performance in growing lambs1

Abstract: This study investigated the effects of dietary protein sources and nisin on rumen fermentation, nutrient digestion, plasma metabolites, N utilization, and growth performance in growing lambs. Thirty-two male Hu lambs (23 ± 2 kg initial BW) were assigned to four dietary treatments in a randomized block design with a 2 × 2 factorial arrangement. Two protein sources, soybean meal (SBM) and dried distillers grains with solubles (DDGS), and two levels of nisin, 0 and 30.5 mg of nisin/kg of feed, were used to formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…In total, 139 metabolites were changed as a result of garlic skin supplementation, 93 out of 139 signi cantly different metabolites had higher concentration including amino acids, dipeptides, fatty acids, and carbohydrates in GAS-fed lambs compared with CON-fed lambs. These amino acids and dipeptides can be used as precursors for the synthesis of microbial protein, while carbohydrates and fatty acids can provide energy for the synthesis of microbial protein [48]. Additionally, our study also demonstrated pyrimidine and purine metabolism pathways were changed in GAS-fed lambs.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In total, 139 metabolites were changed as a result of garlic skin supplementation, 93 out of 139 signi cantly different metabolites had higher concentration including amino acids, dipeptides, fatty acids, and carbohydrates in GAS-fed lambs compared with CON-fed lambs. These amino acids and dipeptides can be used as precursors for the synthesis of microbial protein, while carbohydrates and fatty acids can provide energy for the synthesis of microbial protein [48]. Additionally, our study also demonstrated pyrimidine and purine metabolism pathways were changed in GAS-fed lambs.…”
Section: Discussionsupporting
confidence: 57%
“…Ruminal uid (approximately 25 mL) was collected using an oral stomach tube immediately prior to feeding on the last day of the trial as described by Shen et al (2018) [48]. The pH of the ruminal uid sample was measured immediately after collection using a portable pH meter (Ecoscan pH 5, Eutech Instruments, Singapore).…”
Section: Sample Collection and Measurementmentioning
confidence: 99%
“…However, the influences of DDGS addition on rumen microbial community structure and function in growing lambs remain poorly understood. In our previous study using growing lambs, substituting DDGS for SBM in an isonitrogenous diet increased dietary EE, neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents, and significantly altered rumen fermentation parameters such as volatile fatty acid (VFA) and ammonia concentrations [5].…”
Section: Introductionmentioning
confidence: 99%
“…In lambs, 20% inclusion of DDGS did not affect the dry matter intake (DMI) (Schauer et al, 2008) and improved weight gain (Felix et al, 2012), but when 25% of DDGS was included in the diet, the concentration of ammonia nitrogen in the rumen and the digestibility of DM decreased (Uwituze et al, 2010). However, DDGS could replace soybean meal as a nitrogen (N) source for growing lambs to reduce N excretion without adversely affects animal performance (Shen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%